TEST RESULTS OF A NEW SEEDER FOR SEEDING ONION SEEDS (Journal of Science-Innovative Research in Uzbekistan, 2024)
To develop a new vegetable seeder in relation to the soil and climatic conditions of Uzbekistan and to determine the onion seed rate depending on the length of the active part of the seed coil, as well as to assess the quality of the formation of sowing ridges and irrigation furrows